Cancer Cells Microsurgery via Asymmetric Bent Surface Au/Ag/Ni Microrobotic Scalpels Through a Transversal Rotating Magnetic Field - Vyskočil, Jan; Mayorga-Martinez, Carmen C; Jablonská, Eva; Novotný, Filip; Ruml, Tomáš; Pumera, Martin (ACS nano, 2020)
The actuation of micro/nanomachines by means of a magnetic field is a promising fuel-free way to transport cargo in microscale dimensions. This type of movement has been extensively studied for a variety of micro/nanomachine designs, and a special magnetic field configuration results in a near-surface walking. We developed "walking" micromachines which transversally move in a magnetic field, and we used them as microrobotic scalpels to enter and exit an individual cancer cell and cut a small cellular fragment. In these microscalpels, the center of mass lies approximately in the middle of their length. The microrobotic scalpels show good propulsion efficiency and high step-out frequencies of the magnetic field. Au/Ag/Ni microrobotic scalpels controlled by a transversal rotating magnetic field can enter the cytoplasm of cancer cells and also are able to remove a piece of the cytosol while leaving the cytoplasmic membrane intact in a microsurgery-like manner. We believe that this concept can be further developed for potential biological or medical applications.
Keywords: magnetic field; self-propulsion; micromotors; surface walker; cancer treatment